2020
DOI: 10.1590/0100-3984.2019.0107
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic interstitial pneumonia: computed tomography findings in 36 patients

Abstract: Objective: To analyze the computed tomography (CT) findings of lymphocytic interstitial pneumonia (LIP). Materials and Methods: We retrospectively reviewed the clinical and CT findings of 36 patients with LIP, including 25 women and 11 men, with a mean age of 52.5 years (age range, 22-78 years). Results: The main associated diseases with LIP were Sjögren syndrome (42%), human immunodeficiency virus infection (17%), amyloidosis (17%), Sjögren syndrome associated with secondary amyloidosis (11%), idiopathic (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Lymphocytic interstitial pneumonia (or pneumonitis, LIP) is a rare form of ILD, a benign lymphoproliferative disorder consisting of infiltration of lung tissue with lymphocytes and plasma cells [79].…”
Section: Definitionmentioning
confidence: 99%
“…Lymphocytic interstitial pneumonia (or pneumonitis, LIP) is a rare form of ILD, a benign lymphoproliferative disorder consisting of infiltration of lung tissue with lymphocytes and plasma cells [79].…”
Section: Definitionmentioning
confidence: 99%
“…These lesions can be disseminated, but are located mainly along the bronchovascular bundles, interlobular septa and pleurae. HRCT reveals numerous cysts bilaterally within the pulmonary parenchyma; other possible manifestations include nodules and, less frequently, ground-glass opacities and bronchiectasis [13].…”
Section: Lymphocytic Interstitial Pneumoniamentioning
confidence: 99%
“…A number of recent studies in the radiology literature of Brazil have highlighted the importance of imaging methods in the assessment of the chest( 7 , 8 , 9 , 10 , 11 , 12 ). Among the pulmonary findings on computed tomography scans of the chest, Alves Júnior et al (6) found, in descending order, cysts (in 92.9% of patients), emphysema (in 57.1%), and subpleural bullae (in 42.9%), typically in combination and bilateral.…”
mentioning
confidence: 99%